2017
DOI: 10.1002/gj.2989
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐copper deposits in Wushitala, Southern Tianshan, Northwest China: Application of ASTER data for mineral exploration

Abstract: The Southern Tianshan area is one of the most important gold belts identified by many world‐class, super large and large gold deposits such as Muruntau (Uzbekistan), Kumtor (Kyrgyzstan), and Jilau (Tajikistan). Some medium‐ to small‐scale gold deposits, such as Sawayaerdun and Bulong, have been discovered and reported in recent years at the China part of the belt. The study area, named the Wushitala area, is located in the eastern part of Southern Tianshan, and it has a strong potential for gold and other meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The study area field checking was dominated by a high intensity of hydrothermal alteration, which affected many rocks that embedded mineral types such as chlorite, epidote, muscovite, or sericite, and opaque minerals. The altered mineralized rocks display secondary minerals, which are common indicators of mineralization, such as gold and copper (Gabr, Ghulam, & Kusky, 2010; Han & Nelson, 2014; Liu, Li, Zhou, Han, & Xu, 2018; Ruiz‐Armenta & Prol‐Ledesma, 1998). Zoheir and Emam (2012) found that the alteration area, comprising pyrite, quartz, carbonate, chlorite, sericite, and goethite, hosts several open pits and trenches within quartz veins and boudins in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The study area field checking was dominated by a high intensity of hydrothermal alteration, which affected many rocks that embedded mineral types such as chlorite, epidote, muscovite, or sericite, and opaque minerals. The altered mineralized rocks display secondary minerals, which are common indicators of mineralization, such as gold and copper (Gabr, Ghulam, & Kusky, 2010; Han & Nelson, 2014; Liu, Li, Zhou, Han, & Xu, 2018; Ruiz‐Armenta & Prol‐Ledesma, 1998). Zoheir and Emam (2012) found that the alteration area, comprising pyrite, quartz, carbonate, chlorite, sericite, and goethite, hosts several open pits and trenches within quartz veins and boudins in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The principal component analysis (PCA)-based Crosta technique and band ratio techniques like the Kaufmann and Sabins ratios proved to be more significant and efficient for hydrothermal mineral exploration. Several researchers have also concluded that advanced image processing techniques like those applied and tested in the current study are quite efficient in terms of mineral mapping through remote sensing data (Manuel et al, 2017;Liu et al, 2018). The maps produced in this study are not only appropriate for any spatial queries and analysis, but also for environmental modelling such as assessing the impacts of mining activities on environmental features such Mapping hydrothermal minerals using remotely sensed reflectance spectroscopy data as the forest, farmland, and urban areas.…”
mentioning
confidence: 71%
“…The band combination of shortwave infrared 2 with spectral band 2.11-2.29 μm and near infrared with spectral band 0.85-0.88 μm in Figure 11 shows the areas which have the potential to host clay minerals in shades of red to yellow. Liu et al (2018) applied various image-processing techniques, including false-colour composite, band ratios, and matched filtering, to process ASTER satellite data and map the distribution of hydrothermal minerals associated with gold deposits, and concluded that the SWIR and NIR bands are the most effective for this purpose.…”
mentioning
confidence: 99%
“…In the paper by Liu, Li, Zhou, Han, and Xu ( ) , the authors used various image processing techniques to map hydrothermal minerals related to known deposits in the Wushitala region of Southern Tianshan. A correlation was established between identified alteration zones and known gold–copper deposits in the study area.…”
Section: Volume 3: Structure and Main Themesmentioning
confidence: 99%